URGENSI PSIKOLOGI PENDIDIKAN ISLAM DALAM PENDIDIKAN KADER ULAMA MUHAMMADIYAH - Gunawan, Aris Pratama; Wantini, Wantini (Jurnal Hadratul Madaniyah, 2024)
Muhammadiyah Ulama Cadre Education is an effort and strategy carried out by Muhammadiyah to answer the challenge of the scarcity of ulama in Muhammadiyah. In addition, Muhammadiyah Ulama Cadre Education is also an effort to instill renewal values ​​that are implemented into the personality of a scholar who has broad insight, high intellect, and sensitivity to changing times. To realize this goal, educators are needed who need to master various sciences, one of which is psychology, especially Islamic educational psychology. The approach used in this research is qualitative, the type of literature, with the analysis of the content analysis model. The result of this discussion is the urgency of Islamic education psychology in Muhammadiyah Ulama Cadre Education, namely to understand the development of the student by reviewing the physical and spiritual aspects of the student, conducting learning, and coaching processes that instill Islamic values ​​in shaping human qalbiyah intelligence, Islamic education psychology. build unification and integration in the formation of human personality kaffah, and apply the potentials of students and coaches in coaching and learning.